Answer:
B
Step-by-step explanation:
If you calculate the side of a square using pythagorean theorem, you would get a side length of sqrt37. Simple multiply this by 4
Answer:
<h2>x = 2 </h2><h2>y = - 3</h2><h2>z = - 2</h2>
Step-by-step explanation:
6y - 5z = -8 .......... Equation 1
3z = -6 ................... Equation 2
4x - 3y - 2z= 21...... Equation 3
<u>First solve for z in Equation 2</u>
That's
3z = - 6
Divide both sides by 3
<h3>z = - 2</h3>
Next substitute the value of z into Equation 1 in order to find y
We have
6y - 5(-2) = - 8
6y + 10 = - 8
6y = - 8 - 10
6y = - 18
Divide both sides by 6
<h3>y = - 3</h3>
Finally substitute the values of y and z into Equation 3 to find the value of x
That's
4x - 3(-3) - 2(-2) = 21
4x + 9 + 4 = 21
4x + 13 = 21
4x = 21 - 13
4x = 8
Divide both sides by 4
<h3>x = 2</h3>
So the solutions are
<h3>x = 2 </h3><h3>y = - 3</h3><h3>z = - 2</h3>
Hope this helps you
Theorem
In a triangle, the measure of an exterior angle equals the sum of the measures of its two remote interior angles.
x + y = z
4n - 18 + n + 8 = 133 - 6n
5n - 10 = 133 - 6n
11n = 143
n = 13
z = 133 - 6n = 133 - 6(13) = 133 - 78 = 55
Answer: C. 55
Answer: 3/5
Step-by-step explanation:6/10 6 divide by 2 and 10 divide by 2
hoped this helped:)